The Policy of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency in Land Registration Services during the Covid-19 Pandemic and Its Implications - Nugroho, Dwi Cahyo (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out about the policies of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency in Land Registration Services during the Covid-19 Pandemic and their Implications. Approach method is the normative-empirical method. The specification of this research is analytical descriptive in nature. The data in this study are primary data and secondary data. These problems are analyzed using public policy theory. Based on the results of the research that based on the results of the research that at this time the National Land Agency (BPN) as a government agency that organizes land registration is being constrained in terms of service to the community in carrying out land registration with the Covid-19 Virus Pandemic. The Ministry of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (BPN) issued a Policy in the form of Circular Letter Number 7/SE-100.HR.01/IV/2020 concerning Ease of Services for Determination and Registration of Land Rights during the Emergency Response Status of Corona Virus Disease 2019 (covid-19).Keywords: Land; Pandemic; Policy.